Read Reason Write : - Seyler, Dorothy U. (McGraw-Hill, 2008)
This comprehensive text presents clear instruction on critical reading and analysis, argument, and research techniques, along with a collection of current, incisive readings appropriate for practicing those techniques. New features of the eighth edition include an expanded visual program, featuring new chapter opening visuals and two full-color inserts, and a newly revised and updated reader.